Bingkai Media Menjelang Pemungutan Suara Ulang (PSU) Dewan Perwakilan Daerah Sumatera Barat 2024 - Mento, Meris Essio; Hadi, Sofyan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
In the electoral contestation process, the media does not only convey information, but also plays a role in shaping public opinion through framing an election event. This article analyzes how local online media frames the news ahead of the 2024 Re-Vote (PSU) of the Regional Representative Council of the Republic of Indonesia in West Sumatra in a very short span of time, namely 33 days from the Constitutional Court's decision on June 10, 2024 to the implementation of the election on July 13, 2024. This condition is a crucial issue because the availability of a short time has the potential to hinder the adequate flow of information to voters and affect voter participation. This study uses a qualitative method with Entman's framing analysis model, which includes 4 elements, define problems, diagnose cause, moral judgements, and treatment recommendation. Data was obtained from 68 local online media news (Harian Singgalang, Klikpositif.com, Langgam.id, and TopSumbar.co.id) and analyzed using NVivo 12 software to support the coding and visualization process. The results of the study show that the media tends to frame PSU as a technical-administrative problem with the main cause resulting from the Constitutional Court's decision and implementation challenges in a very short span of time. Moral judgments are more directed at appreciation of election organizers, while framing representations of voter votes tend to be minimal. The solutions offered by the media are normative, such as the appeal to participate and massive socialization. The dominant framing of procedural aspects shows a lack of emphasis on the substance of democracy, and can contribute to low voter participation.